Penguatan Literasi Perbankan Syariah dengan Program Experiential Learning - Bari, Abdul (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The aim of this research is to determine the effectiveness, understanding and practical experience of the literacy skills of IAI Al-Khairat Pamekasan Sharia Banking students through the Experiential Learning program. This type of research is quantitative research with the sample size being the entire population, namely 45 people. The instruments used in this research were questionnaires and interviews. The data analysis technique used was IBM SPSS Statistics 26 software. Based on the results of the data analysis that has been carried out, it shows that the Experiential Learning program has a positive influence on student literacy as shown by the t test results of 0.000 which is smaller than ? = 0.05. Experiential Learning has an effect of 76.5% as shown by the results of the Determination Test. Experiential Learning provides a learning approach that emphasizes direct experience as a means of gaining understanding and skills.